Recent Advances in Organic Synthesis Based on N,N-Dimethyl Enaminones - Huang, Jiuzhong; Yu, Fuchao (Synthesis, 2020)
Enaminones are gaining increasing interest because of their unique properties and their importance in organic synthesis as versatile building blocks. N,N-Dimethyl enaminones offer a better leaving group (a dimethylamine group) than other enaminones, and allow further elaboration via a range of facile chemical transformations. Over the past five years, there have been an increasing number of reports describing the synthetic applications of N,N-dimethyl enaminones. This review provides a comprehensive overview on the synthetic applications of N,N-dimethyl enaminones that have been reported since 2016.1 Introduction2 Direct C(sp2)–H α-Functionalization2.1 Synthesis of α-Sulfenylated N,N-Dimethyl Enaminones2.2 Synthesis of α-Thiocyanated N,N-Dimethyl Enaminones2.3 Synthesis of α-Acyloxylated N,N-Dimethyl Enaminones3 Functionalization Reactions via C=C Double Bond Cleavage3.1 Synthesis of Functionalized Methyl Ketones3.2 Synthesis of α-Ketoamides, α-Ketoesters and 1,2-Diketones3.3 Synthesis of N-Sulfonyl Amidines4 Construction of All-Carbon Aromatic Scaffolds4.1 Synthesis of Benzaldehydes4.2 Synthesis of the Naphthalenes5 Construction of Heterocyclic Scaffolds5.1 Synthesis of Five-Membered Heterocycles5.2 Synthesis of Six-Membered Heterocycles5.3 Synthesis of Quinolines 5.4 Synthesis of Functionalized Chromones5.5 Synthesis of Other Fused Polycyclic Heterocycles6 Conclusions and Perspectives
Keywords: N,N-dimethyl enaminones; C(sp2)–H α-functionalization; cyclization reactions; C=C double bond cleavage; heterocycles